Key Fire Disaster Prevention Factors in Informal Settlements in Nairobi - Maina, Samuel; Ngau, Peter (University of Nairobi, 2020)
The study aimed to examine the dynamics of fire disaster, vulnerability and response in the informal settlements in Nairobi using a case study of Mukuru Fuata Nyayo, a constellation of informal settlements lying in the southern side of the city. In Kenya, there is no systematic record by government and city authorities on fires in informal settlements. There are often sporadic and conflicting reports on fire occurrence by diverse organizations and agencies, including the Kenya Red Cross Society (KRCS), the United Nations Office of the Coordination of Humanitarian Affairs (UN-OCHA) and the Kenya National Disaster Operations Centre (NDOC). For example, for the period between January and March 2011, KRCS reported that approximately 42 fire incidences occurred resulting in at least 11 fatalities and about 472 casualties in Nairobi’s informal settlements (KRCS, 2015). For the same period, UN-OCHA reported that 71 fires occurred in Nairobi resulting in loss of 2,016 jobs, 376 houses, 2 deaths, 11 casualties and asset loss above US$ 1 million (UN-OCHA, 2011).
Keywords: Informal Settlements